Use of Acellular Dermal Matrix for the Treatment of Gingival Recession: Case Report - González Quesada DDS, MSc, Jorge (2016)
Among the procedures for treatment of gingival recession using subepithelial connective tissue , the use of acellular dermal matrix is an accepted choice for root coverage . The present article reports the treatment of gingival recessions using the acellular dermal matrix ( Alloderm® ) and Flap Tunnel Technique.